Evolution and architecture of a West Mediterranean Upper Pleistocene to Holocene coastal apron‐fan system. Issue 2 (3rd August 2013) - Andreucci, Stefano; Panzeri, Laura; Martini, I. Peter; Maspero, Francesco; Martini, Marco; Pascucci, Vincenzo
Abstract The Quaternary deposits of tectonically stable areas are a powerful tool to investigate high‐frequency climate variations (<10 ka) and to distinguish allogenic and autogenic factors controlling deposition. Therefore, an Upper Pleistocene–Holocene coastal apron‐fan system in north–western Sardinia (Porto Palmas, Italy) was studied to investigate the relations between climate changes, sea‐level fluctuations and sediment source‐supply that controlled its development. The sedimentary sequence records the strong influence of local (wet/dry) and worldwide (sea‐level) environmental variations in the sedimentation and preservation of the deposits. A multi‐disciplinary approach allowed subdivision of the succession into four major, unconformity‐bounded stratigraphic units: U1 U2, U3 and U4. Unit U1, tentatively dated to the warm and humid Marine Isotopic Stage (MIS) 5, consists of sandy, gravelly coastal/beach deposits developed during high sea‐level in low‐lying areas. Unit U2 consists of debris‐flow dominated fan‐deposits (ca 74 ka; MIS 4), preserved as partial fills of small valleys and coves. Unit U2 is mainly composed of reddish silty conglomerate to pebbly siltstones sourced from the Palaeozoic metamorphic inland hills (bedrock), superficially disintegrated during the preceding warm, vegetation‐rich MIS 5. The cold and semi‐arid climate strongly reduced vegetation cover along the valley flanks. Therefore, sediment gravity‐flow processes, possibly activated by rainstorms, led to deposition of debris‐flow dominated fans. Unit U3 consists of water‐flow dominated alluvial‐fan deposits (ca 47 to 23 ka; MIS 3), developed on a slightly inclined coastal plain. Unit U3 is composed of sandstone and sandy conglomerate fed from two main sediment sources: metamorphic inland bedrock and Quaternary bioclastic‐rich shelf‐derived sands. During this cold phase, sea‐level dropped sufficiently to expose bioclastic sands accumulated on the shelf. Frequent climate fluctuations favoured inland aeolian transport of sand during dry phases, followed by reworking of the aeolian bodies by flash floods during wet phases. Bedrock‐derived fragments mixed with water‐reworked, wind‐blown sands led to the development of water‐flow dominated fans. The Dansgaard–Oeschger events possibly associated with sand landward deflation and main fan formations are Dansgaard–Oeschger 13 (ca 47 ka), Dansgaard–Oeschger 8 (ca 39 ka) and Dansgaard–Oeschger 2 (ca 23 ka). No record of sedimentation during MIS 2 was observed. Finally, bioclastic‐rich aeolianites (Unit U4, ca 10 to 5 ka; MIS 1), preserved on a coastal slope, were developed during the Holocene transgression (ca 10 to 5 ka; MIS 1). The studied sequence shows strong similarities with those of other Mediterranean sites; it is, however, one of the few where the main MIS 4 and MIS 3 climatic fluctuations are registered in the sedimentary record.